Does entrepreneurship education in the first year of higher education develop entrepreneurial intentions? The role of learning and inspiration. Issue 3 (4th March 2018) - Nabi, Ghulam; Walmsley, Andreas; Liñán, Francisco; Akhtar, Imran; Neame, Charles
Abstract : Drawing on entrepreneurship education (EE) theory, this article examines the role of learning and inspiration in developing students' entrepreneurial intentions in the First Year in Higher Education. This addresses the paucity of research on early university experiences of EE and their influence on entrepreneurial intentions. Using a longitudinal survey of business students at a British university, the authors identify four scenarios related to the participation/non-participation in EE and subsequent increase or decrease of entrepreneurial intentions. A sub-set of those surveyed are interviewed ( n = 49) to better understand how their university experience has influenced their entrepreneurial intentions. Findings suggest that the influence of EE is variable, in some cases even leading to a decrease in entrepreneurial intentions. The results contribute to theories of EE and intentions in the early stages of higher education. The authors discuss implications for theory and practice.